PROFIL PENGELOLAAN LABORATORIUM BIOLOGI DALAM MENDUKUNG KEGIATAN PEMBELAJARAN DI SEKOLAH MENENGAH ATAS (SMA) NEGERI PEKANBARU - Rosaulidia.S '; Yuslim Fauziah Fauziah; Arnentis ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is a descriptive study that aimed to determine the profile of the management of biological laboratories in supporting learning activities in Senior High School (SMA) Negeri Pekanbaru. This research carried out in SMA Negeri in July until November 2014. The population of this study is SMA Negeri Pekanbaru with samples SMA N 1, 3, 4, 5, 6, 8, 10, and 12 Pekanbaru. The technique used purposive sampling. Data retrieved by using the enclosed quistionnaire were distibuted to teachers of subjects biology class X, XI, and XII. The number of teacher who completed a questionnaire enclosed is as much as 3 people each school. Questionnaires were collected as many as 24, then performed data processing based on indicators that have been determined. Direct observation is done at each school biology laboratory research sample. The observation was also made based on indicators that have been determined that; laboratory design, laboratory administration, laboratory management, and storage and lab materials. The result of the questionsnaire of indicators planning is 3,20 with good criteria, indicator arrangement is 3,32 with good criteria, administrating indicator is 3,16 with good criteria, the security indicator is 3,18 with good criteria, maintenance indicator is 3,52 with good criteria, and monitoring indicators is 2,68 with sufficient criteria. The result above show that the overall management of biological laboratories in SMA Negeri Pekanbaru already included in both criteria and has supported learning activities biology. Key words: management, biology lab, SMA Negeri Pekanbaru